ANALISIS KEBIJAKAN PEMBANGUNAN RUSUNAWA KABUPATEN KENDAL - Yudiantoro Eko Kusumo; Wiwik Widayati; Puji Astuti (Journal of Politic and Government Studies, 2015)
ABSTRACT One of the basic human needs that having important role in life was housing and settlement. The increasing of shelter needs could not having balance with infrastructure development. In addition, the increasing of population density effected the city, caused it populous. This occurrence was not having a balance with the economical ability of local community. The house price got expensive and low income community using various way to survive, built house on the illegal site was one of the way, it was called slum. The alternative to solved this problem was providing mass housing like rusunawa, such as in Kendal. The objective of this study research was to find the decent value of rusunawa’s development in Kabupaten Kendal, whether an appropriate alternative residential treatment compared to other alternative. This study used qualitative research methods and the research design is descriptive qualitative. The location was in Kabupaten Kendal, while the subject was Dinas Ciptaru, Bappeda, and local community around especially the ones who lived on riverside of Sungai Kalireyeng and been relocated. The primary data source was obtained from interview and the secondary data was from journals, archives, documents, and so on. The result showed that the policy of rusunawa development was only fulfilling the physical needs as shelter, and the direct advantage not yet to been felt by the majority of local community. Development rusunawa considered to excessive because the number of residents affected by the relocation of only 45 heads of families. Another alternative could be a simple settlement. But the construction of high-rise apartment in the future development of the district Kendal today. Recommendations for Dinas Ciptaru as the Administrator of Rusunawa Kebondalem was to redo the evaluation, then looked for the points of the development policy’s problem, so that solution could be found to improved the policy further. After that, Dinas Ciptaru could improve the coordination between the agency, central or local agency, for better management. Giving more information about Rusunawa, or giving suggestion to local community to make them interested in using Rusunawa Kebondalem as one of facility provided by government. Keywords: Policy Analysis, Rusunawa, Slums